2005
DOI: 10.1002/ejic.200401060
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium(V) Oxoperoxo Complexes with Side Chain SubstitutedN‐Salicylidenehydrazides: Modeling Supramolecular Interactions inVanadium Haloperoxidases

Abstract: Keywords: Hydrogen bonds / Oxidative bromination / Peroxo ligands / Salicylidenehydrazide ligand / VanadiumThe Schiff-base ligand derived from salicylaldehyde and γ-hydroxybutanoic acid hydrazide (H 2 Salhyhb) reacts with potassium metavanadate and hydrogen peroxide in a water/ methanol solution with a pH value of around two to yield the corresponding vanadium(V) oxoperoxo complex [VO(O 2 )-HSalhyhb(H 2 O)] (1). Complex 1 crystallizes with one molecule of water as 1·H 2 O in the monoclinic space group P2 1 /n.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 88 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…In vanadium(V) complexes, the (HVO 4 ) 2-group is well known and present in numerous structures [22][23][24]. However, until now a (HVO 4 ) 2-group was not found among purely inorganic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…In vanadium(V) complexes, the (HVO 4 ) 2-group is well known and present in numerous structures [22][23][24]. However, until now a (HVO 4 ) 2-group was not found among purely inorganic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Plass [59] reported that a N-salicylidene alkoxo vanadium(V) oxoperoxo complex which has, in the solid state, a pentagonalbipyramidal coordination geometry, with a side-on bonded peroxo ligand in the equatorial plane, is able to brominate, under stoichiometric conditions, 1,3,5-trimethoxybenzene (TMB) in the presence of tetrabutylammonium bromide (90% yield). More recently Xing et al reported that oxovanadium(IV)-carboxylate complexes are effective systems in the bromination reaction of phenol red to bromophenol blue in phosphate buffer [60].…”
Section: Haloperoxidationsmentioning
confidence: 99%
“…[12] We have recently reported the application of the N-salicylidene hydrazide ligand system for generating vanadium(V) complexes with a variety of functional groups attached to the ligand core. [7,8,13,14] Extending this approach, we report herein the synthesis and structure of a cis-dioxovanadium(V) complex containing an appropriate apolar biphenyl group in the ligand side chain, and its inclusion compound with β-CD.…”
Section: Introductionmentioning
confidence: 99%
“…Examples for such vanadium complexes derived from N-salicylidene hydrazides with a hydroxy substituted side chain have recently been reported. [7,8] An alternative method to provide such an environment for the complex moieties can be through their interaction with appropriate host molecules, which would generate host-guest assemblies. Cyclodextrins (CDs) represent hosts tallizes with additional water molecules in the triclinic space group P1.…”
Section: Introductionmentioning
confidence: 99%